Growing Millennial Farmers Through Entrepreneurship Ecosystem - Hariri, Acep; Amar, Mochamad; Alfian, M. Noor; Renika, Anggi (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2025)
Agriculture plays an important role in meeting the increasing food needs of the Indonesian people. However, challenges such as limited land, the El Niño phenomenon, and the limited age span of farmers are significant obstacles. This study aims to develop an entrepreneurial ecosystem model for millennial farmers in East Java Province through the Structural Equation Modeling (SEM) approach using SmartPLS 4.0 software. Data were collected through a survey of 1,588 respondents who were beneficiaries of the Youth Entrepreneur and Employment Support Services (YESS) Program in five districts, using a purposive sampling method. The study result showed that banking and training factors had the most significant influence in encouraging the growth of young entrepreneurs in the agricultural sector. Cooperatives and business partners also contributed to increasing millennial farmers' access to capital, business assistance, and marketing of agricultural products. Meanwhile, government policies and the role of the Agricultural Extension Center (BPP) were considered less optimal in supporting the development of young entrepreneurs. Hence, policies that were more responsive to the needs of millennial farmers were needed. This study provides strategic recommendations for the government and stakeholders to strengthen the agricultural entrepreneurship ecosystem through more inclusive access to capital, sustainable training, and strengthening cooperatives and business partnerships to increase the competitiveness of millennial farmers in the agribusiness sector.